The Communist manifesto - Marx, Karl, 1818-1883; Engels, Friedrich, 1820-1895 (Signet classic., 2011)
The political tract in which Marx presented the core of his philosophy and revolutionary program, with an introduction analyzing its significance to the realities of today and to Marx's own times.